2023
DOI: 10.1111/bph.16000
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the core concepts of pharmacology education: A global initiative

Abstract: In recent decades, a focus on the most critical and fundamental concepts has proven highly advantageous to students and educators in many science disciplines. Pharmacology, unlike microbiology, biochemistry, or physiology, lacks a consensus list of such core concepts.Experimental Approach: We sought to develop a research-based, globally relevant list of core concepts that all students completing a foundational pharmacology course should master. This two-part project consisted of exploratory and refinement phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In the first stage of the process in 2022, ‘ agonists and antagonists ’ were identified as a core concept of pharmacology (White et al, 2023). However, at the Prato meeting, it was decided to separate agonists and antagonists for ease of definition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first stage of the process in 2022, ‘ agonists and antagonists ’ were identified as a core concept of pharmacology (White et al, 2023). However, at the Prato meeting, it was decided to separate agonists and antagonists for ease of definition.…”
Section: Resultsmentioning
confidence: 99%
“…In the first stage of this international project (White et al, 2023), the IUPHAR‐Ed Core Concepts of Pharmacology expert group identified 25 core concepts of pharmacology that higher education students studying foundational courses in pharmacology should know, understand and be able to apply after graduation. This paper describes the next stages of the project.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations